Membangun Platform E-commerce ESERRA Berbasis Flutter - WIJAYA, HERMAN (Sains Manajemen: Jurnal Manajemen Unsera, 2024)
In the continuously evolving digital era, e-commerce has become one of the main pillars supporting economic growth and innovation. This research aims to develop a Flutter-based e-commerce platform at the University of Serang Raya (UNSERA) to foster entrepreneurship among students, faculty, and staff. The development of this platform is designed to enhance transaction efficiency and effectiveness, control product quality, and improve transaction security. By utilizing modern technologies such as Dart, Flutter, and Laravel, this platform offers solutions to address the challenges of traditional e-commerce, focusing on rapid development, application performance, and optimal user experience. The study includes a needs analysis, design, implementation, and evaluation of an e-commerce application prototype. It is expected that this platform will create an ecosystem that supports business growth and innovation within the academic environment, shaping a generation of young entrepreneurs ready to compete in the global market. The research findings indicate that this platform is capable of increasing transaction efficiency and facilitating the development of the creative economy within the academic community at UNSERA.